2016
DOI: 10.15320/iconarp.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Satisfaction and Environmental Preferences of Students

Abstract: This study seeks to explore the role of university campus quality in art students' satisfaction. Environmental satisfaction is one of the key criteria by which the extent of university educational quality may be determined. An educational environment of high quality campus conveys a sense of satisfaction with university environment that may be physical, social and symbolic. Satisfaction and dissatisfaction from the art students' point of view can be used as criteria for the campus planning, design and manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results of this study indicated that the high lecturer's environmental satisfaction on the environmental characteristics of campus campuses on the aspects of the physical environment and humanitarian aspects relative to the research conducted by [6]. The study also conducts research on environmental satisfaction of Turkish students on campus campus environments on physical, social, and symbolic aspects.…”
Section: Resultsmentioning
confidence: 68%
“…The results of this study indicated that the high lecturer's environmental satisfaction on the environmental characteristics of campus campuses on the aspects of the physical environment and humanitarian aspects relative to the research conducted by [6]. The study also conducts research on environmental satisfaction of Turkish students on campus campus environments on physical, social, and symbolic aspects.…”
Section: Resultsmentioning
confidence: 68%